The Rule of Law Crisis and its Implications on National Security in Pakistan - Imran, Muhammad; Kazmi, Dr. Syedah Sadia (Journal of Political Studies, 2025)
The rule of law is an essential pillar for sustaining democracy, human rights and economic development, yet Pakistan faces a profound crisis in this domain that significantly threatens its national security. This study explores the multidimensional impacts of the rule of law crisis in Pakistan contribute to social unrest and undermine the state's capacity to address both internal and external security challenges. Using mixed-methods approach, this research combines quantitative surveys of legal professionals and security officials to capture diverse perspectives on the erosion of judicial independence and its implications for public trust and institutional integrity. The study aims to identify key relationships between the rule of law crisis and critical security sectors, including political and societal security. By addressing how weak rule of law exacerbates human insecurity, poverty, and social inequality, the research underscores the necessity for reform to restore public confidence in legal institutions. The findings will provide valuable insights for policymakers seeking to foster a stable and just governance framework, reinforcing the rule of law as fundamental to Pakistan’s national security. Ultimately, this work contributes to the ongoing dialogue regarding the intersections of law, governance and security in the context of a complex geopolitical landscape.